2017
DOI: 10.1111/pbi.12844
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic repertoires depict the initiation of lint and fuzz fibres in cotton (Gossypium hirsutum L.)

Abstract: SummaryCotton fibre is an important natural fibre for the textile industry. The number of fibre initials determines the lint percentage, which is an important factor for cotton fibre yield. Although fibre development has been described by transcriptomic analysis, the mechanism by which the long noncoding RNA manipulates the initiation of lint and fuzz fibres remains unknown. In this study, three lines with different lint percentages were developed by crossing Xu142 with its fibreless mutant Xu142 fl. We collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…The lncRNAs and circular RNAs were identified, and of these, 645 and 651 lncRNAs were preferentially expressed in the fibreless and fibre‐attached lines, respectively. Via a virus‐induced gene silencing (VIGS) approach, down‐regulation of three lncRNAs increased the fibre initial numbers significantly (Hu et al ., ). Another study also identified more than 35 000 lncRNAs and showed their potential functions in fibre development of G. barbadense (Wang et al ., ,).…”
Section: The Mechanisms Of Epigenetic Modifications In Cotton Fibre Dmentioning
confidence: 97%
“…The lncRNAs and circular RNAs were identified, and of these, 645 and 651 lncRNAs were preferentially expressed in the fibreless and fibre‐attached lines, respectively. Via a virus‐induced gene silencing (VIGS) approach, down‐regulation of three lncRNAs increased the fibre initial numbers significantly (Hu et al ., ). Another study also identified more than 35 000 lncRNAs and showed their potential functions in fibre development of G. barbadense (Wang et al ., ,).…”
Section: The Mechanisms Of Epigenetic Modifications In Cotton Fibre Dmentioning
confidence: 97%
“…In cotton, previous studies have shown that lncRNAs XLOC_063105-CotAD_37096 and XLOC_115463-CotAD_12502 probably function in cis-regulating responses to drought stress [32]. One lncRNA, TCONS_00061835-Gh_D06G1439 (GhMYB-like), regulates cotton fiber development [36] by complementary base pairing with the protein-coding gene, lncRNA, and the circRNA complex network, demonstrating that some lncRNAs are involved in biotic and abiotic stresses [31,33,34].…”
Section: Lncrna In the Anther Development Of Cotton And Predicted Funmentioning
confidence: 99%
“…In cotton, lncRNAs participate in resistance to Verticillium dahliae [31], drought stress [32], salt stress [33], and other abiotic stresses [34]. LncRNAs also participate in regulating fiber development [5,35] and in lint initiation [36]. However, little is known about the mechanisms of lncRNA during the cytoplasmic male sterility (CMS) in cotton; therefore, it is necessary to identify novel lncRNA and analyze the lncRNA in the development of cotton anther.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of cotton genome G. raimondii (Paterson et al ., ; Wang et al ., ), G. arboreum (Li et al ., ) and upland G. hirsutum (Li et al ., ; Zhang et al ., ) sequences has enabled the use of RNA‐Seq for cotton transcriptomic studies. Previous studies have shown the efficacy of transcriptomic and proteomic data sets for understanding the molecular mechanisms of begomovirus and whitefly infestation on tomato and cultivated cotton G. hirsutum (Li et al ., ; Zhao et al ., ), cassava mosaic begomovirus infection on cassava (Allie et al ., ), tomato yellow leaf curl virus (TYLCV) infection on tomato (Chen et al ., ; Hasegawa et al ., ; Huang et al ., ), geminivirus infection on pepper (Gongora‐Castillo et al ., ) and other pathways related to begomovirus (Brustolini et al ., ) and cotton development (Hu et al ., ).…”
Section: Introductionmentioning
confidence: 97%